SAT0121 Oral morphine versus oral hydromorphone in rheumatologic non-malignant pain: a prospective randomised study in 144 patients. (1st June 2001) - Grilo, R; Di Fazano, C Scoto; Coyral, D; Bertin, P; Bonnet, C; Treves, R
Abstract : Background: Morphine and hydromorphone are commonly used as opioids in cancer pain. The management of non-malignant pain is sometime difficult. A recent and debated therapeutic consideration is the used of morphine in intractable Rheumatologic Non-Malignant Pain (RNMP). Objectives: The purpose of this prospective randomised study was to compare the efficacy of pain relief and side effects of oral hydromorphone and oral morphine in RNMP. Methods: 144 patients suffering from RNMP were assigned to receive oral morphine or oral hydromorphone. Different criteria were affeffed: dose of morphine (mg/day), duration of treatment (days), baseline and post-treatment evaluation of pain using a Visual Analogic Scale (VAS, in cm). The prevalence of nausea was assessed in the two groups. Results: Conclusion: We observed a VAS mean decrease of 3.7 cm with oral hydromorphone and 4 cm with oral morphine, despite oral hydromorphone provides no statistical significant benefit over oral morphine in RMNP.